Disturbo della quieta pubblica (Disturbing the peace). Psicoanalisi dell’autodistruzione in Richard Yates: John Wilder (ENTHYMEMA, 2020)
From a psychoanalytic point of view, the work examines the character of John Wilder, protagonist of Disturbing The Peace by Richard Yates of 1975. Some significant extracts from the novel and the plot are presented, followed by a psychoanalytic reflection that explores the psychic economy of the character. Masochism is here identified, as postulated by Freud and some post-Freudian authors, an instance that represents a derivative of the death drive and a paradoxical structure of the whole psychic life. One wonders how unconscious masochism acts in the character's actions, how it influences his defeat but also his singular resource, and how all this is articulated with hope, from which John, like all Yates characters, is particularly conditioned.